The European TREatment of ATopic eczema (TREAT) Registry Taskforce survey: prescribing practices in Europe for phototherapy and systemic therapy in adult patients with moderate‐to‐severe atopic eczema. (18th March 2020) - Vermeulen, F.M.; Gerbens, L.A.A.; Schmitt, J.; Deleuran, M.; Irvine, A.D.; Logan, K.; Ouwerkerk, W.; Vestergaard, C.; Flohr, C.; Spuls, P.I.; ,
Summary: Background: For many years dermatologists have had access to few therapies for patients with moderate‐to‐severe atopic eczema (AE). New promising therapies are entering the market but conventional phototherapies and systemic therapies have more well‐known safety profiles, lower costs and wider availability. Objectives: To provide insight into current prescribing practices of conventional phototherapy and systemic immunomodulatory therapies for adults with chronic AE, and the factors influencing these prescribing practices, before biologics and other novel therapeutics become routine clinical practice. Methods: In this exploratory study dermatologists were invited to participate in an online survey via a mailing list of the European Academy of Dermatology and Venereology and national societies. Data were collected on participant characteristics (including clinical practice data), the use of phototherapies and systemic therapies, and factors influencing their use. Results: From 30 European countries, 238 out of 361 dermatologists willing to participate (65·9%) completed the survey, with 229 meeting the inclusion criteria. For phototherapy (prescribed by 84·7%), most preferred narrowband ultraviolet B as first line (80·9%) and psoralen plus ultraviolet A as second (21·6%). For systemic therapy (prescribed by 95·2%) ciclosporin (54·1%), oral corticosteroids (32·6%) and methotrexate (30·7%) were used first line. Dermatologists relied mostly on personal experience for prescribing phototherapy and systemic therapy. Azathioprine and mycophenolic acid were prescribed by only 135 (59·0%) and 85 (37·1%) participants in total, mostly due to a lack of personal experience. Conclusions: This study provides insight into prescribing practices for conventional phototherapy and systemic therapy in Europe and shows that off‐label therapies are also preferred as first‐line choice of systemic therapy. Abstract : What is already known about this topic? Varying prescribing practices were found for adult (in the UK) and paediatric (in Northern America and Europe) patients with moderate‐to-severe atopic eczema (AE). Not much is known about the prescription of phototherapy and (off‐label) systemic therapy for adult patients in Europe. Although therapies like dupilumab are promising new treatment modalities, better‐known safety profiles, lower costs and better availability are reasons to improve the evidence profile of conventional systemic therapies like ciclosporin. What does this study add? Prescribing practices of European dermatologists treating adult patients with moderate‐to-severe AE show diversity. Most dermatologists prefer narrowband ultraviolet B as first‐line phototherapy, followed by psoralen plus ultraviolet A as second line. Next to ciclosporin, which is most commonly prescribed, (off‐label) methotrexate and oral corticosteroids are also frequently used as first‐line systemic agents in chronic AE. Lack of personal experience with azathioprine and mycophenolic acid was the most important reason against their prescription. What are the clinical implications of the work? The results from this study might help to improve the experience with, and prescribing of, all available conventional phototherapies and (off‐label) systemic therapies. Guidelines developers might use these results to develop and implement treatment algorithms. Linked Comment: Bruin‐Weller. Br J Dermatol 2020; 183 :987–988 . Plain language summary available online